Dietary spray-dried plasma enhances the growth performance, villus:crypt ratio and cold-induced stress resistance in Nile tilapia (Oreochromis niloticus) - Araújo, Eric Portilho de [UNESP]; Carvalho, Pedro Luiz Pucci Figueiredo de [UNESP]; Freitas, Jakeline Marcela Azambuja de [UNESP]; Silva, Rafael Lopes da [UNESP]; Rocha, Mariucha Karina Honório Ribeiro [UNESP]; Teixeira, Caroline Pelegrina [UNESP]; Damasceno, Flavia Mota [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP] (Elsevier, 2017)
Nutritional strategies can help fish manage stress, and functional feedstuffs are an interesting nutritional option. Therefore, this study evaluated the potential functional effect of spray-dried plasma (SDP) on Nile tilapia growth performance and the capacity of SDP to improve fish health under cold-induced stress (CIS). A total of 440 fish (12.64 ± 0.64 g) were randomly distributed into 40,250-L aquaria and fed five diets containing graded levels of SDP (0, 16.6, 33.2, 49.7 and 66.3 g kg− 1) for 60 days. The growth performance, villus height:crypt depth ratio, and hematological parameters were analyzed, and the same hematological parameters were then analyzed after 7 days of CIS. Based on the broken-line analysis of the FBW, SGR, RWG and FCR, the optimum dietary level supplementation of SDP was determined to be 49.70, 50.16, 51.83 and 41.83 g kg− 1 diet, respectively. The crypt depth and villus:crypt ratio were positively affected by SDP supplementation. After CIS, hematocrit of fish fed 16.6 g kg− 1 of dietary SDP was significantly lower than fish fed 66.3 g kg− 1 level (P < 0.05). The supplementation level of dietary SDP and the CIS affected the leukocyte, lymphocyte and neutrophil counts. The monocyte count was affected by the dietary SDP supplementation level both before and after CIS (P < 0.05). Total plasma protein concentration in the fish fed 49.7 and 66.3 g kg− 1 SDP were significantly higher than fed 16.6 g kg− 1 SDP after CIS (P < 0.05), and CIS led to a higher Albumin:Globulin ratio (P < 0.05). Dietary SDP supplementation improved the growth performance, intestinal health, hematological profile and CIS resistance of the studied fish. Based on our results, we recommend a dietary supplementation level of 51.83 g kg− 1 SDP for Nile tilapia.
Keywords: Hematology; Immunonutrition; Intestinal morphometry; Oreochromis niloticus; Spray-dried plasma; Temperature stress